Evaluasi Sistem Teknologi dan Penyimpanan dalam Rantai Pasok Halal Rumah Potong Unggas - Adenan, Moh; Wahyu Prianto, Fajar; Subagio, Ari; Wulandari, Deasy; Prasetiyaningtiyas, Susanti; Cholifah, Umi; Irmadariyani, Ririn (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2025)
Indonesia, with the world’s largest Muslim population, has significant potential to lead the global halal ecosystem, particularly in the poultry slaughterhouse (RPU) sector. However, limited halal-certified RPUs, inadequate technology, and storage infrastructure remain critical challenges. This study aims to identify key performance indicators of halal certification for RPUs in Jember Regency, evaluate their supply chain performance, and develop strategic recommendations. A mixed methods approach with an explanatory sequential design was employed, beginning with qualitative interviews and FGDs, followed by a quantitative survey involving 73 respondents across six stakeholder groups. Results indicate storage aspects received the highest performance ratings, while technology lagged behind. SWOT analysis revealed strengths such as strong consumer awareness and opportunities from government support and emerging technologies, counterbalanced by infrastructure weaknesses and regulatory threats. The study recommends enhancing cold storage capacity, training halal personnel, and implementing digital traceability systems. These findings offer both practical and theoretical contributions to strengthening RPU roles within Indonesia’s broader halal ecosystem.